2004
DOI: 10.1086/422475
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of 13 Genome Scans Reveals Multiple Cleft Lip/Palate Genes with Novel Loci on 9q21 and 2q32-35

Abstract: Isolated or nonsyndromic cleft lip with or without cleft palate (CL/P) is a common birth defect with a complex etiology. A 10-cM genome scan of 388 extended multiplex families with CL/P from seven diverse populations (2,551 genotyped individuals) revealed CL/P genes in six chromosomal regions, including a novel region at 9q21 (heterogeneity LOD score [HLOD]=6.6). In addition, meta-analyses with the addition of results from 186 more families (six populations; 1,033 genotyped individuals) showed genomewide signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
206
0
4

Year Published

2005
2005
2011
2011

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 201 publications
(225 citation statements)
references
References 39 publications
(48 reference statements)
7
206
0
4
Order By: Relevance
“…The green arrows indicate the 1 and 2 log odds ratio intervals of linkage. Modified from [20]. The location of the TP63 gene is defined by the blue arrows.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The green arrows indicate the 1 and 2 log odds ratio intervals of linkage. Modified from [20]. The location of the TP63 gene is defined by the blue arrows.…”
Section: Resultsmentioning
confidence: 99%
“…The first CL/P scan was performed on 92 British sibpairs and identified a total of nine regions with suggestive results [49]. This has been followed by five additional scans of varying size (Table 2) [20,24,[49][50][51][52][53][54]. In general, the results have been modest with the exception of a log odds ratio (LOD) score of 3.0 at 17p13.1 in a scan of two large Syrian families [50].…”
Section: Genome Scans Identify Novel Locimentioning
confidence: 99%
“…Moreover, the 1.27 Mb region of 9q21 was included in previously reported candidate locus of cleft lip/palate by meta-analysis of linkage analysis. 24 The patient K16 actually had velopharyngeal insufficiency due to the submucous cleft palate. Therefore, it is reasonable to consider the deleted genes cooperated with development of a cleft palate, which is often accompanied by KS.…”
Section: Discussionmentioning
confidence: 99%
“…Egfr, Bmp4, Bmpr1 and Folbp1) (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Eight genome scans have identified regions that may potentially harbor NSCLP susceptibility genes (19)(20)(21)(22)(23)(24)(25). In 2000, Prescott et al (26) identified nine chromosomal regions that are associated with orofacial clefting in their Caucasian NSCLP sib-pair population.…”
Section: Introductionmentioning
confidence: 99%